The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/en12050834
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Life Cycle Energy and GHG Emission Analysis for BEVs and PhEVs: A Case Study in China

Abstract: Battery electric vehicles (BEVs) and plug-in hybrid electric vehicles (PHEVs) are seen as the most promising alternatives to internal combustion vehicles, as a means to reduce the energy consumption and greenhouse gas (GHG) emissions in the transportation sector. To provide the basis for preferable decisions among these vehicle technologies, an environmental benefit evaluation should be conducted. Lithium iron phosphate (LFP) and lithium nickel manganese cobalt oxide (NMC) are two most often applied batteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 31 publications
2
43
1
Order By: Relevance
“…In our study, the battery and vehicle production, vehicle use, and vehicle maintenance stages contribute to the GWP of NMC-BEV by 48%, 51%, and 1%, respectively. These percentages appear to be consistent with [31,54]. NMC-BEV has less impact than DIE-ICEV on GWP (−32 %) and CED (−12%) and this is consistent with the results of [31] (−45% and −20%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the battery and vehicle production, vehicle use, and vehicle maintenance stages contribute to the GWP of NMC-BEV by 48%, 51%, and 1%, respectively. These percentages appear to be consistent with [31,54]. NMC-BEV has less impact than DIE-ICEV on GWP (−32 %) and CED (−12%) and this is consistent with the results of [31] (−45% and −20%, respectively).…”
Section: Discussionsupporting
confidence: 90%
“…IPCC suggested that the global warming potentials of CH 4 and N 2 O relative to CO 2 should be set to 28 and 265, respectively, based on cumulative forcing over 100 years [64]. Emission factor of electricity was set to 726 g CO 2 -eq/kWh because researchers reported that the production of 1kWh electricity generated 715 to 736.8 g CO 2 -eq in China [65,66]. This value was about the same as emission factor of electricity in Hong Kong at 722 g CO 2 -eq/kWh in which a portion of electricity was generated by nuclear power in Daya Bay Nuclear Power Plant [4,67].…”
Section: Determination Of Energy Use and The Associated Ghg Emission In The Computer Communication And Electronic Product Manufacturing Imentioning
confidence: 99%
“…Therefore, many countries have implemented new energy vehicles (NEVs) as alternatives to conventional vehicles to reduce the dependence on oil and air pollution caused by conventional vehicles [2][3][4]. As the world's largest automotive market, China has been committed to promoting NEVs to reduce the consumption and import of oil [3,5,6]. In Europe, Germany proposes to have one million EVs in operation by 2020 to reduce CO 2 emissions [7][8][9]; France and UK have also aimed to restrict the in-country sale of conventional vehicles by 2040 [2].…”
Section: Introductionmentioning
confidence: 99%